FORMULATION AND EVALUATION OF ANTIPARKINSON’S DRUG INCORPORATED TRANSDERMAL FILMS - POREDDY SRIKANTH REDDY; ALAGARSAMY V; SUBHAH CHANDRA BOSE P; DAMINENI SARITA; SRUTHI V (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Ropinirole suitable for transdermal delivery due to its small molecular size (260.37 g/mol), optimum log p (2.3), and low oral bioavailability (50%) due to first-pass metabolism, the short elimination half-life of 4–6 h. Dose of drug is 6 mg/day. Hence, in the present study, an attempt was made to deliver antiparkinson’s drug through transdermal route in the form of transdermal film to attain sustained release using different concentration of drug, polymers stabilizers. Methods: Among the different formulations of matrix type (F1 to F5), F2 and F4 formulations were optimized based on crystallinity. These formulations were carried out for in vitro permeation studies. Out of these two formulations, F4 formulation showed target drug release. Results and Discussion: The formulation F4 containing 2 mg drug, 600 mg hydroxypropyl methylcellulose E15 and 50 mg of Eudragit RS 100 was selected as optimized formulation, after considering its microscopic examination throughout stability, % drug content (98.4%), drug permeated through the cellophane membrane at the end of 72 h, and evaluation of physicochemical characterization parameters such as thickness, weight variation, flatness, folding endurance, moisture content, and tensile strength. Conclusion: The results of physicochemical characterization were ensured the stability of the films. The drug permeation profile was also found to follow Higuchi kinetic model.